Removal of Direct red 12B Dye in an Integrated Fixed Film Activated Sludge Reactor (IFAS): Performance Evaluation and Kinetics Study - Zahra Godarzvand Chegini; Amir Hossaain Javid; Amir Hesam Hassani (Iranian Journal of Health, Safety and Environment, 2018)
The application of biological treatment has been promising in recent years for the main advantage of biological treatment in COD and dye removal. The novelty of this study is capabilities of integrated fixed film system (IFAS) with a different arrangement of media to removal the dye and COD. The experiments were done with a survey of variables like SRT, MLSS/MLVSS, the initial concentration of dye and COD. In order to analyze data was used the first and second-order models. The result showed that the IFAS was effective even at high concentration of the dye (200mg L-1). COD reduction and dye removal efficiency were higher than 70% and 88-95%, respectively. For the biological treatment, an increase in SRT to 48hr. increased the dye and COD concentration reduction. Kinetics of COD reduction and dye removal was fitted with the second-order reaction by coefficient correlation of 0.95 and 0.97, respectively. Finally, the integration of fixed film media into the biological reactors affected performances of the system for decolorization from colored wastewater.